REPRESENTASI PEREMPUAN BALI DALAM NOVEL “KENANGA” KARYA OKA RUSMINI - Pramesti Arsa, Putu Pradnya; Pradipta, Ade Devia; Alit Suryawati, I Gusti Agung (E-Jurnal Medium, 2020)
Gender injustice occurs because of the values ??about gender that have been deeply embedded inssociety. The mass mediapplays anaimportant roleein this process. How the media presents women is used as a reference to see and "judge" women. The novel "Kenanga" by Oka Rusmini is a fictional writing with the theme of Balinese women. In this novel, Balinese women are portrayed through two sides, namely in custom and also as a modern individual. This study aims to explain the representation of women in the novel "Kenanga” . This study uses a qualitative approach with critical discourse analysis method of Sara Mills. The results of this study indicate that amidst the strong culture of patriarchy in Bali, the figure of Balinese women is represented as an independent individual who is strong and has control over her own life. With this representation of women, the novel "Kenanga" by Oka Rusmini breaks the stereotype of women as weak and passive. Keywords: Novel “Kenanga” , Critical Discourse Analysis, Sara Mills, Balinese Women